Bacterial diseases of dry beans in South Africa with special reference to common bacterial blight and its control - Van Wyk, P.S. (Pieter Schalk), 1944- (University of Pretoria, 2013)
Thesis (PhD (Microbiology))--University of Pretoria, 2005.